A novel sleep optimisation programme to improve athletes' well-being and performance. Issue 2 (7th February 2017) - Van Ryswyk, Emer; Weeks, Richard; Bandick, Laura; O'Keefe, Michaela; Vakulin, Andrew; Catcheside, Peter; Barger, Laura; Potter, Andrew; Poulos, Nick; Wallace, Jarryd; Antic, Nick A.
Abstract: Objectives : To improve well-being and performance indicators in a group of Australian Football League (AFL) players via a six-week sleep optimisation programme. Design: Prospective intervention study following observations suggestive of reduced sleep and excessive daytime sleepiness in an AFL group. Methods : Athletes from the Adelaide Football Club were invited to participate if they had played AFL senior-level football for 1–5 years, or if they had excessive daytime sleepiness (Epworth Sleepiness Scale [ESS] >10), measured via ESS. An initial education session explained normal sleep needs, and how to achieve increased sleep duration and quality. Participants ( n = 25) received ongoing feedback on their sleep, and a mid-programme education and feedback session. Sleep duration, quality and related outcomes were measured during week one and at the conclusion of the six-week intervention period using sleep diaries, actigraphy, ESS, Pittsburgh Sleep Quality Index, Profile of Mood States, Training Distress Scale, Perceived Stress Scale and the Psychomotor Vigilance Task. Results : Sleep diaries demonstrated an increase in total sleep time of approximately 20 min (498.8 ± 53.8 to 518.7 ± 34.3; p < .05) and a 2% increase in sleep efficiency ( p < 0.05). There was a corresponding increase in vigour ( p < 0.001) and decrease in fatigue ( p < 0.05). Conclusions : Improvements in measures of sleep efficiency, fatigue and vigour indicate that a sleep optimisation programme may improve athletes' well-being. More research is required into the effects of sleep optimisation on athletic performance.